(untitled) (ModaPalavra e-periódico, 2016)
The article aims to expose reflections on the handcraft as a symbolic differential for fashion products and design. Thetext presents reflections on the representations of craft production to the consumer market from the study of the categories: commodity fetish and value. Therefore, they were used with theoretical support the concepts erected by Karl Marx and empirical observations on the exploitation of handcraft by the current luxury market, for example. The methodological routes adopted for the construction of research guided in field research, specifically with participant observation, and literature review. The results point to the construction of interesting reflections on the exploitation of cultural goods and elements derived from popular culture as agregators value to drivers of consumption today.